New glass-ceramic from ternary–quaternary mixtures based on Colombian industrial wastes: Blast furnace slag, cupper slag, fly ash and glass cullet - Estefania Montoya-Quesada; Mónica A. Villaquirán-Caicedo; Ruby Mejía de Gutiérrez (Boletín de la Sociedad Española de Cerámica y Vidrio, 2022)
The aim of this research was to evaluate the production of glass ceramics from novel combinations of fly ash, glass cullet, blast furnace slag and copper slag solid wastes. The CaO/SiO2 molar ratios of the mixtures were 0.17–0.39. Glass ceramics were produced by thermal treatment of frits obtained by quenching in water. The results show that samples with a high Fe2O3 content (>4 wt%) are not adequate for glass-ceramic formation, as a result of the effect of ferric iron, Fe3+, which increases the network connectivity, on the stability of the glass. The mechanical properties of the ceramic materials were as follows: elastic modulus of 97.8–106 GPa, Vickers microhardness of 612–701 MPa, fracture toughness of 0.45–0.84 MPa m1/2, and friction coefficient of 0.57–1.0. For the glass ceramics, the mass loss did not exceed 1% in NaOH and 15% in HNO3 as a result of the crystalline phases formed. The ceramic materials developed in this research could be considered for potential applications in the production of glazes for residential or industrial tiles and coatings, among others. Resumen: El principal objetivo de esta investigación fue evaluar novedosas combinaciones de ceniza volante, residuos de vidrios, escoria siderúrgica y escoria de cobre combinados para la obtención de materiales vitrocerámicos. Las mezclas tuvieron una relación CaO/SiO2 de entre 0,17-0,39. Las vitrocerámicas fueron producidas por tratamiento térmico de fritas obtenidas a partir enfriamiento en agua. Los resultados han mostrado que las mezclas con altos contenidos de Fe2O3 (> 4% en peso) no son adecuados para la formación de vitrocerámicas. Estos resultados se asocian a la alta estabilidad del vidrio debido a la presencia de Fe3+, el cual incrementa la conectividad y estabilidad de la estructura vítrea. Las propiedades mecánicas encontradas en los materiales vitrocerámicos fueron: módulo de elasticidad de 97,8-106 GPa, microdureza Vickers de entre 612-701 MPa, tenacidad a la fractura K1c de entre 0,45-0,84 MPa.m1/2, y coeficiente de fricción de entre 0,57-1,0. Las vitrocerámicas tuvieron una pérdida de masa no mayor al 1% en solución de NaOH y del 15% en soluciones de HNO3. Las vitrocerámicas obtenidas en esta investigación podrían considerarse para aplicaciones potenciales como glaseados en placas domesticas e industriales y recubrimientos, entre otros.